Editorial - Belizan, Jose M. (Current Women's Health Reviews, 2006)
Every Women Count The World Health Report 2005 - Make Every Mother and Child Count, says that this year almost 11 million children under five years of age will die from causes that are largely preventable. Among them are 4 million babies who will not survive the first month of life. At the same time, more than half a million women will die in pregnancy, childbirth or soon after. The report says that reducing this toll in line with the Millennium Development Goals depends largely on every mother and every child having the right to access to health care from pregnancy through childbirth, the neonatal period and childhood. All of those who chose to work on women health are aware of the significance of this WHO statement and our willingness is to see the effect of our efforts in every woman of the world and this enormous responsibility has been taken by journal Current Women's Health Reviews. Health equity of women at the highest level possible is the aim to achieve. An avoidable maternal death can not be admitted anymore and the best quality of life in every period for every woman needs to be reached. The present copy of the journal Current Women's Health Reviews is the second volume of the journal. I am happy that journal completes its one year successfully and all the issues of first volume comprise a variety of good articles with up-to-date information regarding every aspects of women's health. My aim as Editor-in-Chief is to provide scholarly publications that are useful to clinicians and obstetricians. This issue also shows a diversity of information with a good balance of contributions to women global health. Researchers from developing and developed countries can provide contributions to attain journal's aim and contribute to achieve the best equalitarian women global health. The issue starts with an article by Olâh gives an update of the surgical management of vesico vaginal fistulae. Up to 80,000 women each year develop fistulae. Between 500,000 and one million women are currently living with fistulae. Many of these women become social outcasts turned out of homes and rejected by their husbands and families. Regardless that every woman in labour should have access to an appropriate control of labour to prevent the fistulae, surgical repair will relief these women and allow their family and social reinsertion. Two articles of this issue referred to contraception, a need of women to avoid grand multiparity and to attain reproductive health. According to WHO,